PELUANG BISNIS MELALUI KEGIATAN KEWIRAUSAHAAN DAN PENGHITUNGAN HARGA POKOK PRODUKSI SERTA HARGA JUAL PRODUK MINUMAN OBAT TRADISIONAL - Lismawati Lismawati; Fadli Fadli; Isma Coryanata; Indah Oktari Wijayanti (LPPM Universitas Bina Bangsa, 2023)
This community service aims to provide skills and knowledge about business opportunities through entrepreneurial activities and calculating the cost of goods produced and selling prices of traditional medicine beverage products. The target group in this service activity is mothers and young women of home industry players in the community of Sri Kuncoro Village, Pondok Kelapa District, Central Bengkulu Regency. Service activities are carried out by providing practices on how to calculate the cost of goods produced and selling prices for traditional ginger medicine drinks. This activity provides results in the form of understanding and knowledge possessed by mothers and young women of home industry players in the community of Sri Kuncoro Village, Pondok Kelapa District, Central Bengkulu Regency about calculating the cost of goods produced and can determine the selling price of home industry products produced